2020
DOI: 10.1177/1473325020973309
|View full text |Cite
|
Sign up to set email alerts
|

Photovoice as a creative coping tool with the COVID-19 crisis in practical training seminar for social work students

Abstract: The Coronavirus-19 crisis has led university professors, social workers, students and social service consumers to shift to online methods of communication and teaching. In this novel, shared reality, the present paper introduces a new initiative based on implemented photovoice methodology as a tool for documenting BSW students' professional daily lives. This tool was used at a practical training seminar for 16 third year students at the School of Social Work, Sapir Academic College.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 1 publication
0
6
0
1
Order By: Relevance
“…Due to restrictions imposed by the current COVID-19 pandemic, participants with access to electronic communication tools will be preferred. 46 47 We anticipate the recruitment of participants with access to electronic communication tools will cause bias in the study results. However, in view of the improved COVID-19 situation in Malaysia and the ability to conduct fieldwork with strict Standard Operating Procedures (SOPs), this bias may be minimised by conducting the study at the study sites and via face-to-face interviews.…”
Section: Methods and Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Due to restrictions imposed by the current COVID-19 pandemic, participants with access to electronic communication tools will be preferred. 46 47 We anticipate the recruitment of participants with access to electronic communication tools will cause bias in the study results. However, in view of the improved COVID-19 situation in Malaysia and the ability to conduct fieldwork with strict Standard Operating Procedures (SOPs), this bias may be minimised by conducting the study at the study sites and via face-to-face interviews.…”
Section: Methods and Analysismentioning
confidence: 99%
“…The study will include participants who are permanent residents of the village, are mobile, without known cognitive or mental health issues, and are able to answer questions in Malay or English language. Due to restrictions imposed by the current COVID-19 pandemic, participants with access to electronic communication tools will be preferred 46 47. We anticipate the recruitment of participants with access to electronic communication tools will cause bias in the study results.…”
Section: Methods and Analysismentioning
confidence: 99%
“…No son muchos los estudios que se han encontrado publicados en los últimos años en los que se haya trabajado con el Photovoice como herramienta pedagógica en el ámbito de ciencias de la salud (Andina-Díaz, 2020;Coronado et al, 2020;Fernandes et al, 2018;Gallagher & Stevens, 2015), así como en otras disciplinas (Malka, 2021;Von Sommoggy et al, 2020). Los resultados de este estudio ayudan a dar consistencia al Photovoice como herramienta válida para tal fin.…”
Section: Discusión Y Conclusionesunclassified
“…Researchers required methods that would allow "direct" access and document meaningful life experiences, perspectives, and priorities (Santana et al, 2021). Some authors (Malka, 2021a(Malka, , 2021bSy et al, 2020) suggested photovoice for remote data collection. Photovoice is participatory action research that combines participants' photographs and voices (Rodrigues et al, 2008;Wang & Burris, 1997) to document life experiences, needs, difficulties, and desires in photographs that are discussed in critical reflection.…”
Section: Introductionmentioning
confidence: 99%